Sleep and circadian rhythms: pillars of health—a Keystone Symposia report. Issue 1 (2nd August 2021) - Cable, Jennifer; Schernhammer, Eva; Hanlon, Erin C.; Vetter, Céline; Cedernaes, Jonathan; Makarem, Nour; Dashti, Hassan S.; Shechter, Ari; Depner, Christopher; Ingiosi, Ashley; Blume, Christine; Tan, Xiao; et al.
Abstract: The human circadian system consists of the master clock in the suprachiasmatic nuclei of the hypothalamus as well as in peripheral molecular clocks located in organs throughout the body. This system plays a major role in the temporal organization of biological and physiological processes, such as body temperature, blood pressure, hormone secretion, gene expression, and immune functions, which all manifest consistent diurnal patterns. Many facets of modern life, such as work schedules, travel, and social activities, can lead to sleep/wake and eating schedules that are misaligned relative to the biological clock. This misalignment can disrupt and impair physiological and psychological parameters that may ultimately put people at higher risk for chronic diseases like cancer, cardiovascular disease, and other metabolic disorders. Understanding the mechanisms that regulate sleep circadian rhythms may ultimately lead to insights on behavioral interventions that can lower the risk of these diseases. On February 25, 2021, experts in sleep, circadian rhythms, and chronobiology met virtually for the Keystone eSymposium "Sleep & Circadian Rhythms: Pillars of Health" to discuss the latest research for understanding the bidirectional relationships between sleep, circadian rhythms, and health and disease. Abstract : Understanding the mechanisms that regulate sleep and circadian rhythms may ultimately lead to insights on behavioral interventions that can lower the risk of cancer, cardiovascular disease, and other metabolic disorders. This report presents the latest research on understanding the bidirectional relationships between sleep, circadian rhythms, and health and disease. On Demand content : https://keysym.us/EK21NYAS